ANALISIS RISIKO HUKUM PENGGUNAAN ROBO-ADVISOR DALAM INVESTASI SAHAM SYARIAH: STUDI ASPEK GHARAR DAN MAYSIR - Yuniartik Yuniartik (Adisam Publisher, 2026)
The development of financial technology (FinTech) has introduced innovations such as Robo-Advisors, digital platforms providing algorithm-based investment management services. In the Sharia capital market, the use of Robo-Advisors presents new challenges concerning compliance with Sharia principles, specifically the prohibition of Gharar (uncertainty) and Maysir (gambling). This research aims to analyze the legal risks of using Robo-Advisors in Sharia stock investment in Indonesia through a normative-juridical approach. The findings indicate that Gharar risk arises from the